Fabrication and characterization of a magnetite water hyacinth nanocomposite for effective Cr(VI) remediation - Tebelay Liknaw Andualem; Ermias Abelneh Tesema; Reddy Prasad D.M. (Scientific Reports)
Abstract Exploring a method for purifying water, this study focused on using a novel biosorbent a nanocomposite made by combining magnetite with water hyacinth – to capture and remove toxic hexavalent chromium (Cr(VI)). The synthesized material underwent thorough examination using techniques like FTIR to identify its surface chemistry, revealing the presence of hydroxyl and carbonyl groups, which likely play a crucial role in binding Cr(VI). The material’s surface charge, indicated by a PZC of 5.3, shifts from positive in acidic conditions to negative in more alkaline environments. Interestingly, embedding magnetite increased the material’s surface area to 237.81 m²/g, offering more sites for adsorption compared to the raw water hyacinth (205.4 m²/g). The effectiveness of this biosorbent was tested under various conditions. The removal of Cr(VI) improved significantly with longer contact times, reaching a peak efficiency of 87.2% after 120 min. Increasing the amount of biosorbent used also boosted removal, achieving 80.5% at the highest dosage tested. However, higher initial concentrations of Cr(VI) made removal slightly less efficient, with the best result (85.8%) observed at a concentration of 25 mg/L. The way Cr(VI) attached to the biosorbent surface closely followed the Langmuir model, suggesting a uniform, single-layer adsorption process. As per Langmuir isotherm the maximum sorption uptake ( qo) is 12.5 mg/g and the pseudo-second-order equation rate constant k2 is 0.00106 (mg*min)/g. Furthermore, the speed of adsorption appeared to be governed by the initial interaction between the Cr(VI) and the biosorbent’s outer layer, aligning with a first-order kinetic model. Overall, the results indicate that this magnetite-enhanced water hyacinth nanocomposite shows considerable promise as an effective material for cleaning up hexavalent chromium contamination in water.